Learning Evaluation at the Darussalam Martapura Islamic Boarding School - Ahmad Faisal (Pesantren Reviews, 2023)
This study aims to explain how the implementation of learning evaluation at Islamic boarding schools is seen from the planning, implementation, monitoring and processing of learning evaluation results data. This research was conducted at the Darussalam Martapura Islamic boarding school. primary data sources as well as documentation techniques as secondary data sources while the analysis used descriptive qualitative analysis techniques. As for the results of this study, the implementation of learning evaluation at the Darussalam Martapura Islamic boarding school has gone well, seen from the first planning of learning evaluation at the Islamic boarding school, only compiling question papers and informing students of the limitations of the material to be tested as in the hadith book of Riyadhus Salihin from page 1 -25, secondly, the implementation of learning evaluation at Islamic boarding schools uses more test evaluation instruments, namely oral tests and written tests, thirdly monitoring at Islamic boarding schools when carrying out evaluations such as nisfu Sanah exams and Sanah final exams monitoring or supervising the implementation of exams and fourthly processing data results evaluation of learning in Islamic boarding schools after implementing the learning evaluation to make corrections andgive scores and grades with a range of 1-10 to the answers from the students are then reported in the form of a student report card.